Evaluation of mobilization efficacy with an extended interval following plerixafor administration. (October 2020) - Stump, Sarah E; Trepte, Morgan; Shaw, J Ryan; Grgic, Tatjana; Ptachcinski, Jonathan R; Sharf, Andrew; Riches, Marcie; Shea, Thomas C; Park, Yara A; Alexander, Maurice D
Plerixafor is a hematopoietic stem cell mobilizing agent used in combination with granulocyte-colony stimulating factor to improve collection for autologous stem cell transplantation. Despite a recommendation for administration 11 h prior to apheresis per package labeling, logistical challenges lead many institutions to administer plerixafor at an extended interval. The purpose of this study was to determine if plerixafor effectively and efficiently mobilizes CD34+ cells when given at an extended interval prior to apheresis. This was a retrospective evaluation of adult patients who received plerixafor based on an algorithm reserving daily plerixafor only for patients with a pre-apheresis CD34+ count of < 20 cells/µL (pre-apheresis plerixafor) or with a low CD34+ yield after the first apheresis session (rescue plerixafor). The primary outcome was achievement of a disease-specific collection goal of ≥ 6 ×10 6 CD34+ cells/kg for multiple myeloma and ≥ 4 ×10 6 CD34+ cells/kg for lymphoma. The mean interval between plerixafor administration and apheresis was 17 h in this study. Despite this extended interval, 64% of patients met their disease-specific collection goal. A minimum collection goal of ≥ 2 ×10 6 CD34+ cells/kg was achieved by 95% of patients. Mobilization remained efficient with a median of two days to complete collection. Based on this data, plerixafor effectively and efficiently mobilizes CD34+ cells when given at an extended interval prior to apheresis.